2013
DOI: 10.5539/ijef.v5n1017
|View full text |Cite
|
Sign up to set email alerts
|

Interest Rate Pass-Through to Macroeconomic Variables: The Nigerian Experience

Abstract: The effectiveness of monetary policy depends on the adjustment response of Central Banks short-term interest rate on the real interest rates charged by commercial banks and ultimately on macroeconomic indicators of investment and consumption in the economy. Thus, the extent of interest rate pass-through largely depends on how effective the process of financial intermediation works and to what extent individual bank characteristics influence or hinder a perfect adjustment of product rates based on market condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…After the test for the order of integration, the next step is to test for co-integration. This test is used to check if long run relationship exists among the variables in the model (Ogundipe & Alege, 2013). This will be carried out using the Johansen technique.…”
Section: Co-integration Testmentioning
confidence: 99%
“…After the test for the order of integration, the next step is to test for co-integration. This test is used to check if long run relationship exists among the variables in the model (Ogundipe & Alege, 2013). This will be carried out using the Johansen technique.…”
Section: Co-integration Testmentioning
confidence: 99%
“…The finding implied that economic developments in Nigeria. Using a fractional cointegration analysis over the period of 1970-2011 [21] investigated the relationship between environmental quality-carbon emissions and economic growth in Nigeria. The study found no significant evidence to support the EKC in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, in order to lessen their impact on future cash flows and profitability, commercial banks must be aware of these risks. An interest rate is the difference between how much money you borrow now and how much money you repay at a later date and it is affected by the macroeconomic environment (Ogundipe & Alege, 2018).…”
Section: Introductionmentioning
confidence: 99%